Construction of ternary PEG200-based DESs lubrication systems via tailoring tribo-chemistry - Yuting Li; Songyu Lan; Yazhou Liu; Cheng Cao; Zicheng Tang; Deyin Deng; Fuyuan Liu; Hao Li; Xiaoqiang Fan; Minhao Zhu (Friction, 2023)
Abstract Designing novel lubricants with easily customized structures, devisable compositions, and simple and economic synthesis over traditional lubricants is critical to fulfilling complex applications, prolonging machine lifetime, and saving energy. Deep eutectic solvents (DESs), which show tunable composition, adjustable structure, easy fabrication, and environmental friendliness, are promising candidates for variable and complicated lubricants applications. To promote the use of DESs as lubricants, a series of PEG200-based DESs with active heteroatoms were fabricated to tailor the tribological performance via tribo-chemistry. Thereinto, PEG200/boric acid (BA) DES shows optimal lubrication performance by forming tribo-chemical reaction film composited of B2O3, iron oxides, and FeOOH, and PEG200/thiourea (TU) DES displays abrasive wear-reducing property by producing FeS tribo-chemical film. Given the excellent abrasive wear-resistance of PEG200/TU DES and friction reduction of PEG200/BA DES, ternary PEG200/BA/TU DESs, composited of PEG200/TU DES and PEG200/BA DES, are first exploited. The ternary DESs possess superior wettability and thermal stability, which render them potential lubricants. Tribological tests of the ternary DESs demonstrate that synergistic lubrication is achieved by forming a transfer film consisting of Fe x B y , BN, B2O3, and FeS. Wherein Fe x B y , BN, and B2O3 increase load bearing of the film, and FeS mitigates severe abrasive wear. The proposed design philosophy of novel DESs as lubricants opens up a unique realm that is unattainable by traditional DESs lubrication mechanisms and provides a platform to design next-generation DESs lubrication systems.